A Bulky Thiyl‐Radical Catalyst for the [3+2] Cyclization of N‐Tosyl Vinylaziridines and Alkenes. (12th May 2016) - Hashimoto, Takuya; Takino, Kohei; Hato, Kazuki; Maruoka, Keiji
Abstract: Thiyl‐radical‐catalyzed cyclization reactions of N ‐tosyl vinylaziridines and alkenes were developed as a new synthetic method for the generation of substituted pyrrolidines. The key to making this process accessible to a broad range of substrates is the use of a sterically demanding thiyl radical, which prevents the undesired degradation of the catalyst.